The Influence of Service Quality and Rebranding on InDrive’s Brand Image - Alpiero Joeval Isabilillah; Ety Dwi Susanti (Universitas KH. Abdul Chalim Mojokerto, 2024)
The growth of the application-based transportation service industry, or ride-hailing, in Indonesia over the past decade has become an interesting phenomenon in the development of the digital economy. This research uses an associative quantitative approach. The sampling technique used is non-probability sampling, specifically purposive sampling. The population in this study consists of students who have used InDrive's online motorcycle taxi services. The sample for this study is 100 respondents. The data collection technique used is a questionnaire. The data analysis method employed is SPSS 27 for Windows, using multiple linear regression analysis, F-test, t-test, and the coefficient of determination. The results of this study conclude that: Service Quality, partially, has a significant influence on InDrive's Brand Image. Rebranding, partially, has a significant influence on Brand Image, and both Service Quality and Rebranding, simultaneously, have a significant influence on the Impact of Service Quality and Rebranding on InDrive's Brand Image.